Design and Development of a Non-volatile Counter for Metered Dose Inhaler (MDI) - Hin, Tsen Vui; Ramli, Nur Ilyani (International Journal of Integrated Engineering, 2018)
In 2014, Global Asthma Report 2014 stated there were 334 million of people in the worldwide suffering of asthma and the population was increased 99 million compared in 2011. Asthma is the leading chronic childhood disease with albatross on affected children and their families. It occurs when the pulmonary airway is blocked or the airways become narrowed and result in difficult breathing. When asthma under attack, asthma patients normally use metered dose inhaler (MDI) to inhale the salbutamol to restore normal breathing. Therefore, MDI currently available in market unable to monitor the remaining amount of puffs available in the MDI canister and may lead problems for the user due to inability to monitor the amount of salbutamol in the MDI canister. Besides this, some manufacturers developed MDI with counter but it had the limitation such as unable to store memory of the last counting value if power failure occurs, uses non-rechargeable battery and are disposable. Hence, this paper is to present the development of a device consist of a non-volatile counter. It is designed using EEPROM to save the memory of the last counting value and to prevent data loss due to power failure. The MDI was installed with the limit switch for counter and the MDI press is attached to MDI canister so that when the user presses both simultaneously then it provides enough pressure to the limit switch to update the counter. The MDI cover is developed to protect the internal connection and to prevent the user from accidently pressing the limit switch. 7.4V Li-ion rechargeable battery was employed to supply power source for system operation. Arduino UNO (ATmega328P) act as microcontroller to control the system operation of this device. The device is capable of displaying the number of used salbutamol puff on the liquid crystal display (LCD). Furthermore, RGB LED is integrated into the device as visualization to indicate the level of salbutamol in the MDI canister. It consists of four levels indication which is high, medium, low and empty canister of used puff. The high level of used puffs is between 0 to 120 puffs with green colour indicator, medium level is between 121 to 160 puffs with yellow/orange colour indicator, low level is between 161 to 199 puffs with red colour indicator and empty canister without any colour of indicator when the used puffs reached to 200. This device could remind the user to prepare a new MDI canister since it had indicated of low level of salbutamol in the MDI canister. Besides this, it also could reduce the deaths from asthma due to the user would prepare a new MDI canister before attacked by asthma.